EFEKTIVITAS IMPLEMENTASI PILAR MANAJEMEN BERBASIS SEKOLAH DI SEKOLAH DASAR PROVINSI LAMPUNG - Ambarita, Alben (Jurnal Pendidikan Progresif, 2016)
The Effectiveness of School-Based Management Pilar Implementation in The Elementary School of Lampung Province. The purpose of this study was to analyze and describe the effectiveness of the implementation of MBS in core or coaches elementary school which received the input of MBS 2014. The research approach used was qualitative case study design about the effectiveness of the implementation of the curriculum management, students, educators, infrastructure, financing, school relationship with the community, and the environment and culture of the school. Source of the research data were the superintendent, principals, teachers, administrative staff committees and core/coaches elementary schools in five (5) SD of five (5) districts/cities in Lampung. The data collecting technique was using interview, observation and documentation study. The data analysis used Miles and Huberman interaction model which were data collection, data reduction, data presentation and conclusion. The results showed that the implementation of school-based management has been running effectively and involving stakeholders, but has not been supported by the availability of supporting documents. Keywords: effectiveness, school-based management, primary school DOI: http://dx.doi.org/10.23960/jpp.v6.i2.201601